The Double Face Effect Of Algae Extracts As Bio-Pesticides Against Fall Armyworm, Spodoptera Frugiperda, And Root-Knot Nematodes, Meloidogyne Incognita (International Journal of Environmental Sciences, 2025)
Background The fall armyworm (FAW), Spodoptera frugiperda, and root-knot nematode, Meloidogyne incognita, are the most harmful agricultural pests, as they can persist in many environmental conditions and have a broad host range. Therefore, it is necessary to employ several control strategies, such as using biopesticides to reduce their population. This study aimed to designate and evaluate the effects of different concentrations of two methanolic algal extracts, Nostoc muscorum (Cyanobacteria) and Chlorella vulgaris (Chlorophyta), on 3rd instar FAW larvae and 2nd instar juvenile nematode stage (J2s) as a biological environmental strategy.Results Two algal extracts were evaluated against two dangerous plant pests. Subsequently, the expression profiles of acetylcholinesterase and cytochrome P450 genes will be studied. Both algal extracts had clear insecticide and nematicide effects, as shown in the results. Both extracts' highest concentration (100%) resulted in significantly higher mortality rates, which recorded 73% and 67% for FAW larvae and 94% and 88% for J2s, respectively. The expression levels of SfAChE, SfCYP9A60, MiAChE1, and MiCYP were lowered significantly when both target pests were treated with 75% N. muscorum after 24 hours post-treatment. The laboratory bioassay demonstrated that the extracts were highly biopesticide-active at 100% and 75% concentrations, which suppressed the immune response of FAW larvae and M. incognita to invade the host.Conclusions The two algal extracts resulted in various deficiencies in the normal growth and reproduction of insects and root-knot nematode larvae. This caused several issues, including a high mortality rate among FAW larvae, a reduced pupation percentage, and the production of abnormal pupae and moths, as well as juvenile mortality and a decrease in egg hatching rates in nematodes. Given that these algae are easily accessible and extensively cultivated, they can be effectively used by small-scale farmers to control fall armyworms and root-knot nematodes without relying on harmful chemical pesticides, thereby minimizing environmental pollution.